Learning Disorders in Neuroscience and Islamic Education Perspectives - Amin, Khoirul; Sari, Ana Kurnia; Suryana, Ermis; Sutarto, Sutarto; Suhono, Suhono (Graduate Program Magister Manajemen Pendidikan, 2024)
This study examines the learning problems of neuroscience perspectives and Islamic education. To find out what are the factors of learning disorders with a view of neuroscience and Islamic education itself. Neuroscience as a field of science that studies the nervous system in the brain, while Islamic education has great urgency for life. The research uses qualitative methods of literature study by analysing and understanding related to the phenomenon of learning disorders, views of neuroscience and Islamic education. Research with relevant literature sources, this research technique includes summarizing data, and making conclusions. The findings in this study that symptoms of learning disorders in students can be diagnosed from learning outcomes that are not in accordance with the efforts made, slow in completing tasks and then behaviours such as lying, opposing, and lack of confidence. Disorders in neuroscience perspective learning such as Learning Disability, Dyslexia, dyscalculia, ADHD. While in the perspective of Islamic education there are internal factors with intelligence, enthusiasm and patience. While external factors such as cost, guidance, teachers, and quantity of learning.